Why do Patients Stay in Opioid Maintenance Treatment?. (12th May 2014) - Gutwinski, Stefan; Bald, Lena Karoline; Gallinat, Jürgen; Heinz, Andreas; Bermpohl, Felix
<x xml:space="preserve">Abstract</x> Opioid maintenance treatment (OMT) successfully improves social functioning and leads to an increase of survival rates, by reducing drug-related mortality and infections. A region-wide anonymous survey was performed to evaluate subjective factors that could potentially contribute to growing numbers of patients in OMT in the city of Berlin, Germany. In the survey, performed in 2011, 46 staff members and 986 patients participated. Both patients and staff members report beneficial effects of OMT on physical and mental health, and reduction of criminality. Patients on average consider the detoxification from OMT more difficult than from heroin. Staff members underestimate the wish of patients to reach abstinence of OMT. We conclude that besides reduced mortality, these subjective factors may contribute to a growing number of patients in OMT. No financial or material support was received in any phase of the study.